Party games : getting, keeping, and using power in Gilded Age politics - Summers, Mark W. (Mark Wahlgren), 1951- (University of North Carolina Press, 2004)
Much of late-nineteenth-century American politics was parade and pageant. Voters crowded the polls, and their votes made a real difference on policy. Mark Wahlgren Summers tells the story and admires much of the political carnival, but adds a cautionary note about the dark recesses: vote-buying, election-rigging, news suppression, and violence.